2018
DOI: 10.1111/nph.15581
|View full text |Cite|
|
Sign up to set email alerts
|

The Phytophthora sojae RXLR effector Avh238 destabilizes soybean Type2 GmACSs to suppress ethylene biosynthesis and promote infection

Abstract: Phytophthora pathogens secrete many effector proteins to manipulate host innate immunity. PsAvh238 is a Phytophthora sojae N-terminal Arg-X-Leu-Arg (RXLR) effector, which evolved to escape host recognition by mutating one nucleotide while retaining plant immunity-suppressing activity to enhance infection. However, the molecular basis of the PsAvh238 virulence function remains largely enigmatic.By using coimmunoprecipitation and liquid chromatography-tandem mass spectrometry analysis, we identified the 1-aminoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 76 publications
(98 reference statements)
0
50
0
Order By: Relevance
“…Although effectors may often have redundant function, several individual effectors are keys to the full virulence of pathogen. For example, AVH241 and AVH238 could induce cell death and promote infection of P. sojae in N. benthamiana (Yu et al, 2012;Yang et al, 2017Yang et al, , 2019. Therefore, we hypothesized that 26 effectors might regulate the plant defense responses to contribute to virulence of P. viticola.…”
Section: Discussionmentioning
confidence: 99%
“…Although effectors may often have redundant function, several individual effectors are keys to the full virulence of pathogen. For example, AVH241 and AVH238 could induce cell death and promote infection of P. sojae in N. benthamiana (Yu et al, 2012;Yang et al, 2017Yang et al, , 2019. Therefore, we hypothesized that 26 effectors might regulate the plant defense responses to contribute to virulence of P. viticola.…”
Section: Discussionmentioning
confidence: 99%
“…Since its publication, the authors of Yang et al . () have brought to our attention an error in their article. In Fig.…”
mentioning
confidence: 94%
“…For example, some effectors have been shown to both directly hijack plant resistance pathways (King et al ., ; Du et al ., ) and exploit plant susceptibility factors (Yang et al ., ; He et al ., ). Other effectors were reported to suppress plant immunity by interfering with general host cellular processes, including endoplasmic reticulum (ER) stress (Jing et al ., ), autophagosome formation (Dagdas et al ., ), epigenetic regulation (Qiao et al ., ; Kong et al ., ; Hou et al ., )), pre‐mRNA splicing machinery (Huang et al ., ) and phytohormone signaling pathways (Boevink et al ., ; Yang et al ., ). These studies revealed that oomycete effectors evolved to target a variety of host regulatory proteins and thereby interfere with the host defense network and potentially other processes to facilitate infection.…”
Section: Introductionmentioning
confidence: 99%